PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN, RISIKO DAN KEPERCAYAAN TERHADAP KEPUTUSAN MENGGUNAKAN UANG ELEKTRONIK (QRIS) - Alfani, Rizal Syahri; Ariani, Kurnia Rina (ITB AAS Indonesia Surakarta, 2024)
Abstract This research was conducted with the aim of finding out the influence of perceived benefits, perceived convenience, risk and trust on the decision to use QRIS electronic money. This research applies a quantitative approach method. The sampling technique uses purposive sampling. Data was obtained using a questionnaire with 96 respondents using the Slovin formula. The measurement scale used is the Likert scale. The data was processed using SPSS version 23. The results of this research showed that perceptions of benefits, risks and trust had a positive and significant influence on the decision to use QRIS electronic money. Meanwhile, the perception of convenience has a negative influence on the decision to use QRIS electronic money. Keywords: Decision to use, perceived benefits, perceived convenience, risk, trust.